Formation of a Methodological Model of investment audit - V. A. Yakimova; S. V. Pankova (Учёт. Анализ. Аудит, 2022)
The paper considers the reasons that actualize the need for an investment audit, reveals its concept as a special type of audit service. The generalization of the existing positions of scientists on the applied methods and procedures of investment audit revealed the leading role of analytical procedures used to provide this service. The subject of the study is an investment audit as a segment of the activities of external and internal auditors. The purpose of the study is to form conceptual approaches and a methodological model of investment audit. The authors used general scientific principles and research methods: systematization, induction and deduction, synthesis and analysis. The empirical basis was statistical data and scientific works of Russian and foreign scientists. The article discusses the reasons that actualize the need for investment audit, reveals its concept as a special type of this service. n the course of the work, the analysis of factors influencing management decisions in the field of investments was carried out. Also, there were determined the audit tasks for each stage of the investment project and regulatory regulations; the methods used for investment audit and internal control were generalized. The paper consists the conceptual and methodological models of investment audit, revealing its principles, methods, prerequisites, information sources, control points. The results of the study have theoretical and applied significance as well as can be used by researchers in the field of financial control, auditors, business entities.